2020
DOI: 10.12973/ijem.6.2.455
|View full text |Cite
|
Sign up to set email alerts
|

Primary School Teacher Candidates’ Views of Citizenship and Ideal Citizenship

Abstract: <p style="text-align: justify;">Citizenship is an act of being the ideal member of a society that “maintains and adapts to the culture of this society”, besides having a legal status with the duties and rights that the state imposes on the individual. This study aims to determine the citizenship perceptions of primary school teacher candidates and their ideal citizenship narratives.  The study was carried out according to the mixed research design. Three different measurement tools were used in the resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Some managers have an idealism that the understanding, management, curriculum, and activities in Islamic boarding schools must be returned to the Al-Quran and Assunnah without accommodating culture, local wisdom, nationalism, and Pancasila as the ideology of the Indonesian nation (Suharto, 2017;Syafieh & Noviandy, 2022;Kamaluddin et. al., 2022;Turgay, 2020), and transnationalism in education which is counterproductive to the ideology of the Indonesian nation which is essentially by Islamic law (Agustian, 2022). This has created a stigma in society that radicalism and terrorism are attached to Islamic educational institutions such as Islamic boarding schools (Malik, 2017;Acep et.…”
Section: Introductionmentioning
confidence: 99%
“…Some managers have an idealism that the understanding, management, curriculum, and activities in Islamic boarding schools must be returned to the Al-Quran and Assunnah without accommodating culture, local wisdom, nationalism, and Pancasila as the ideology of the Indonesian nation (Suharto, 2017;Syafieh & Noviandy, 2022;Kamaluddin et. al., 2022;Turgay, 2020), and transnationalism in education which is counterproductive to the ideology of the Indonesian nation which is essentially by Islamic law (Agustian, 2022). This has created a stigma in society that radicalism and terrorism are attached to Islamic educational institutions such as Islamic boarding schools (Malik, 2017;Acep et.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, the field of social studies education has a relationship between citizenship skills (Öntaş & Koç, 2020) and political socialization (Öntaş et al, 2020). Teacher qualifications of social studies course, which has a central importance in the development of citizenship skills, can also be discussed.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that each factor is closely related to each other. Moreover, it has direct and indirect effects on global citizenship, both from the same variable level and the different levels (Damrongpanit, 2019b;Ontas & Koc, 2020;Snijders & Bosker, 1993).…”
Section: Introductionmentioning
confidence: 99%